Solusi Al-Qur’an Terhadap Ujaran Kebencian - Moh. Bakir (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
This article wants to explore the Qur'anic view of the utterances of hate with the approach of the theory of maṣlaḥah Najmuddin al-Ṭufi in the book Risālah fī Ri’āyah al-Maṣlaḥah. The author's findings indicate that the Al-Qur'an as a universal scripture emphasizes the importance of safeguarding actions that have the potential to cause noise, conflict, social disintegration and hurt others, both in the form of speech, attitudes, and actions. While the maṣlaḥah according to imam al-Ṭufi is one whose existence gives rise to harmony and does not cause tyranny or harm to anything and anyone. So provocative actions, such as naming, pitting, hoaxes, spreading hate speech and things that can ignite anger from other parties can be suppressed if both pay attention to common concerns. According to him, legally, if an action is clear, the prohibited argument in the text is like the prohibition of cursing, pitting sheep, utterances of hatred, hoax, adultery, gambling, khamar and so on, then the law is forbidden even though these things have a good element for some people especially the culprit.